Development of insulation oil based on Palm Oil Mill Effluent with nano silica - Sidik, Muhammad Abu Bakar; Amalia, Dewi; Agustina, Tuty Emilia; Dinata, Noer Fadzri Perdana; Fitria, Syarifa; Anwar, Wiwin Armoldo Oktaviani (Universitas Mercu Buana, 2024)
Various studies and research have been conducted to find alternatives to liquid insulation. One that is considered the most potential is vegetable oil since it has various advantages, including non-toxic, biodegradable, renewable waste products due to reactions in the form of CO2 and water, high flash points, and better thermal characteristics. In this study, Palm Oil Mill Effluent (POME) was used as the raw material for insulation oil with the addition of an additive in the form of nano-silica, which improves the quality of the insulation oil. As for determining the feasibility of insulation oil, characteristic tests were carried out in the form of density, viscosity, moisture content, acid number, pour point, flash point, and breakdown voltage. Based on the results of the tests, it was obtained that the lowest density in pure oil was 0.8757 g / cm³, the lowest viscosity in oil with the addition of 0.13 wt% nano-silica was 4.0248 cSt, and the lowest acid number in pure oil was 0.5797 mgKOH / g. It was also discovered that the pour point value is the same for each sample, the moisture content is 0.05%, the flashpoint is > 104 °C, and the breakdown voltage is ≥ 60 kV for each sample. The data show that the insulation oil made from POME has the potential to be used as an alternative to insulation oil.